Preparation and evaluation of captopril microspheres by spherical crystallization - Jayaswal S.B.; Reddy T.S.R.; Vijay Kumar M.; Kumar Gupta V. (My University, 2025)
Sustained release captopril microspheres were prepared by spherical crystallisation technique using Acrylic polymers (Eudragit RL 100 and Eudragit RS. 100) and Ethyl cellulose as the matrix. The microspheres were spherical. By using this technique microspheres with diameter in the range of 150-300 um and incorporation efficiency of 40-65% were obtained. The effects of drug to polymer ratio and stirring rate during the preparation on the drug release rate was investigated. Increase in the concentration of the polymer decreased the drug release rate significantly. The most retardant effect was obtained using Eudragit RS. 100. Increase in the stirring rate increased the drug release rate. Release data were examined kinetically and the mechanism was also discussed. Dissolution data indicated that release followed Baker-Lonsdale spherical matrix model kinetics.